Der Darfurkonflikt: Arabische und Afrikanische Identitäten - Justina Rauch (Historia.scribere)
Violent disputes and wars are often explained by tensions based on ethnic or racial grounds. A prominent example is Darfur. Many believe that the origins of the conflict lie in the difference between Arabs and Africans. This paper argues that African and Arab identities have been formed and fostered in the course of the conflict by individual potentates and politically motivated interest groups. Although the African Union was established on the ideas of panafricanism it has failed to alleviate the division between Africans and Arabs.